Predicting research fund management performance using logistic regression: A case study of Universiti Tun Hussein Onn Malaysia (UTHM) research projects / Siti Nabilah Syuhada Abdullah - Abdullah, Siti Nabilah Syuhada (2014)
Established in January 2006, ORICC or Office for Research, Innovation, Commercialization and Consultancy Management of University Tun Hussein Onn Malaysia, Johor, has become the main drive force to enhance research culture and activities at the university. ORICC has created many bold ideas to increase the university’s research quantities and qualities, including the creation of bold mission and vision of research at UTHM. This study aims to analyze the current performance of these funds and find out factors which influences the researchers fund management performance. It can provide assistance in identifying groups of researchers which must be advised about their research expenditure and identify possible team manager candidates that are capable of managing the research project financially in the future. A logistic regression approach was used and it was discovered that a team manager’s age, faculty and the research project’s grant type affects the research project’s fund management status. It was found that research projects who are funded by internal grants are twice more likely to fail in managing their funds than research projects funded by external grants. In terms of team managers’ faculty, when compared to FKMP, team managers from PPD have the highest risk of failing to manage the research project funds followed by team manager from FPTV, FSTPI, FKEE and FPTP. Besides that, research projects with more team members are more likely to fail in managing their research fund compared to research project with fewer team members